(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A number of Social Safety Net Programs (SSNPs) are the measures taken by the government of Bangladesh in order to reduce the portion of its population vulnerability to natural disaster. Bangladesh has a comprehensive portfolio of both food, cash and income generating technology based SSNPs. This study assessed the current status of SSNPs and its effectiveness in Bagerhat (cyclone and coastal flood prone) and Gaibandha (river flood prone) districts. Specially, the study depicted SSNPs within the view of natural hazards (climatic change impacts shocks, floods, cyclones and storm surges, flash floods, drought, tornadoes and landslides). This study showed that the organizational performance in the delivery of SSNPs as well as its technical guidance provided to task teams and program managers for identifying indicators of governance and service quality in the targeted SSNPs programs. This study identified that the governance issues along the results chain of service delivery and suggested policy and performance indicators for assessing the program had a significant impact of the outcome of the SSNPs. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22052 J. Environ. Sci. & Natural Resources, 6(1): 123-129 2013